Pengaruh Customer Engagement Terhadap Brand Loyalty pada Platform Booking.Com yang Dimediasi oleh Brand Attechment dan Customer Trust - Kartika Sari Artamevia; Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of customer engagement on brand loyalty on the Booking.com platform, with brand attachment and customer trust as mediating variables. The research method used is a quantitative causal approach, utilizing primary data obtained through an online questionnaire from Booking.com users in Indonesia who meet the sample criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) model evaluation via SmartPLS 3 software. The results show that customer engagement has a positive and significant effect on brand loyalty, brand attachment, and customer trust. Brand attachment and customer trust also serve as mediators that strengthen the relationship between customer engagement and brand loyalty. This study suggests further research by expanding the sample and adding relevant variables, as well as for companies to enhance customer engagement through personalization and loyalty program reinforcement.